The greatest challenges and solutions to improve children's health and well-being worldwide in the next decade and beyond: Using complex systems and implementation science approaches - Tyack, Zephanie (Frontiers in Pediatrics, 2023)
The health and well-being of children is paramount to health and well-being of society and is the foundation of health and well-being later in life. This paper presents the perspective that a complex systems approach that embeds implementation science is needed to address the rising challenges to child health and well-being in this decade (2020–2030) and beyond. Reflection on facilitators of the success of programs deemed promising to address child health and well-being in the past decade (2010–2020) is presented, to advance programs to address children’s health and well-being. A priority that needs to be addressed is developing, testing and using theories of child and family health and well-being (and related initiatives) that can be used to build on existing successes to make progress. Understanding context including further elucidating the drivers of child health and well-being at multiple levels of relevant systems (e.g., health, education, community) across the life course, and considering implications for caregivers also require greater consideration. Methods to address future challenges to child health and well-being include co-designing initiatives that support child health and well-being with children and families themselves rather than using predesigned initiatives, thoughtful outcome selection, and reporting the challenges of implementing future programs to promote learning. The approaches, priorities and methods presented can be used to design or refine interventions, models or care or community-based initiatives and provide new direction to fields of child health enquiry.